Transforming Economic Law in the Digital Age: Challenges and Opportunities - Nakazawa Atsushi; Zhang Huaizheng; Gachard Sandra (Yayasan Adra Karima Hubbi, 2024)
Research Background: The digital age has significantly changed various aspects of life, including economic law. Digital transformation creates new challenges that require adjustments in the legal framework of economics to accommodate technological innovation. These challenges include e-commerce regulation, personal data protection, cybersecurity, and digital financial transactions. Research Objectives: This study identifies and analyzes the challenges and opportunities in transforming economic law in the digital era. A key focus is updating existing regulations to address digital challenges and taking advantage of existing opportunities to strengthen economic and legal systems. Research Method: This research uses a qualitative approach with literature study methods and document analysis. Data was collected from various sources, including academic literature, government reports, and applicable regulations. The analysis was conducted by comparing and contrasting multiple views and rules related to digital economy laws in several countries. Research Results: The results show that many countries are still in the early stages of adjusting their economic and legal regulations to the development of digital technology. Some critical challenges identified were regulatory vagueness, lack of personal data protection, and cybersecurity threats. However, there are also significant opportunities, such as increased transaction efficiency, ease of global market access, and the potential for inclusive digital economy development. Research Conclusion: This study concludes that the transformation of economic law in the digital age requires a comprehensive and adaptive approach. Regulations must be updated to address challenges and take advantage of existing opportunities. Governments, regulatory agencies, and businesses must collaborate to create legal frameworks that support innovation while protecting the public interest. Effective implementation of regulations will increase public trust and strengthen the digital era's economic and legal system.